PENGARUH MOTIVASI, DISIPLIN, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU (STUDI EMPIRIK PADA SMK PANCASILA SUMBA BARAT DAYA) - Melania Erni; M.E Perseveranda; Anggraeny Paridy (ITB AAS Indonesia Surakarta, 2024)
This study aims to determine the effect of motivation, discipline, and work environment on teacher performance at SMK Pancasila, Southwest Sumba. The research method used is quantitative research. The results of the study showed that the teacher's performance at Pancasila Vocational School Sumba Barat Daya was